Forming the Character of Discipline and Responsibility Through Character Education - Aryadiningrat, Intan Nabila Lestari Hakiem; Sundawa, Dadang; Suryadi, Karim (Indonesian Values and Character Education Journal, 2023)
A nation with strong character can become a nation with dignity and respect by other nations in the world. There is a discipline which is a very important character to be applied in the previous educational environment and in tertiary institutions besides the responsibility discipline character education which is very important to be applied in the everyday environment. Seeing the current condition of students, students have experienced a decline in terms of applying the character of discipline and character of responsibility in carrying out lecture assignments. This study aims to analyze the character of discipline and responsibility through character education, describing the views of lecturers in shaping the character of discipline and responsibility in tertiary institutions. The research method used is qualitative research where the data collection technique is to review literature books, journal entries that have something to do with the problem being discussed. The results of the study can be concluded that in the implementation of discipline and responsibility character education for students there are internal and external factors that affect the decline in discipline and loss of student responsibility. One way to remove these obstacles is through habituation which can change the character of student discipline and responsibility. Character education in tertiary institutions is needed to form and develop students to become individuals with character and strengthen the character acquired by students at the previous level.